2022
DOI: 10.3389/fpls.2022.1051725
|View full text |Cite
|
Sign up to set email alerts
|

Yield and quality of alfalfa (Medicago sativa L.) in response to fertilizer application in China: A meta-analysis

Abstract: IntroductionIn China, alfalfa (Medicago sativa L.) often grows in marginal land with poor soil fertility and suboptimal climate conditions. Alfalfa production cannot meet demands both in yield and quality. It is necessary to apply fertilizers to achieve high yields and produce high-quality alfalfa in China. However, there is no understanding on the impact of fertilizer application on alfalfa production and the possible optimal application rates across China.MethodsWe conducted a meta-analysis to explore the co… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

2
18
0

Year Published

2023
2023
2025
2025

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 15 publications
(20 citation statements)
references
References 65 publications
2
18
0
Order By: Relevance
“…The low cell wall and lignin concentrations caused by salt addition are responsible for the decreased ADF and NDF ( Oliveira et al., 2020 ). A meta-analysis showed that the CP concentration of alfalfa increases with N supply, which is due to the higher activity of key enzymes for N metabolism ( Geisseler et al., 2010 ; Wan et al., 2022 ). However, N supply did not change the CP concentration of alfalfa in this study ( Figure 6D ).…”
Section: Discussionmentioning
confidence: 99%
“…The low cell wall and lignin concentrations caused by salt addition are responsible for the decreased ADF and NDF ( Oliveira et al., 2020 ). A meta-analysis showed that the CP concentration of alfalfa increases with N supply, which is due to the higher activity of key enzymes for N metabolism ( Geisseler et al., 2010 ; Wan et al., 2022 ). However, N supply did not change the CP concentration of alfalfa in this study ( Figure 6D ).…”
Section: Discussionmentioning
confidence: 99%
“…Feeding alfalfa can substantially improve animal’s growth, reproduction, meat and milk production ( Laroche et al., 2022 ; Ma et al., 2022 ; Motsinger, 2022 ). Alfalfa is currently the most commonly cultivated forage crop in China ( Wan et al., 2022 ). Ningxia is located in the northwest agricultural and pastoral ecotone in China.…”
Section: Introductionmentioning
confidence: 99%
“…Reasonable fertilisation management and timely supplements of nutrients deficient in the soil (Bahulikar et al 2020 increase the yield and quality of alfalfa (Wei et al 2018). Fertilisation is a direct approach to improve the yield and quality of alfalfa (Fang et al 2021, Wan et al 2022. Many studies have explored the effects of fertiliser applications on the yield and quality of alfalfa (Fang et al 2021, Wan et al 2022).…”
mentioning
confidence: 99%
“…Fertilisation is a direct approach to improve the yield and quality of alfalfa (Fang et al 2021, Wan et al 2022. Many studies have explored the effects of fertiliser applications on the yield and quality of alfalfa (Fang et al 2021, Wan et al 2022). However, the results have varied substantially or were contradictory due to differences in cuttings, cultivars, water supply, soil, and environmental factors.Applying fertiliser significantly increases alfalfa quality (Wan et al 2022), and alfalfa crude protein (CP), acid detergent fibre (ADF), and neutral detergent fibre (NDF) reflect its nutritional quality…”
mentioning
confidence: 99%
See 1 more Smart Citation